The cult of St. Anne in medieval and early modern Europe - Welsh, Jennifer (Sanctity in global perspective, 2017)
Constructing St. Anne -- Relics, images, and miracles: encountering St. Anne -- Anne, mother of mothers -- Sacred and secular economies -- From holy kinship to holy household -- Decline, transformation, and revival -- St. Anne's Baroque revival